Analisis Perbaikan Cacat Produk pada Proses Produksi Pensil dengan Tahapan DMAIC - solihin, solihin; Fahroni, Aldiwa Alfa Thira Nur; Sumanto, Sumanto; Siregar, Denny (Journal of Industrial and Engineering System, 2021)
Some companies produce the same product and it will make competition between companies. The company must be able to maintain its existence by increasing the efficiency and quality of its products. The company has established product defect tolerance standards. However, during January-December 2020 there were product defects as many as 6,674 pcs of pencils or 0.233% of defective products. This study was conducted to analyze the causes of defective products using the DMAIC. There were three dominant defects found in the analyze, which were 1834 pcs of dirty lead, 1670 pcs of rough pencil surface, and 1669 pcs of cracked pencil. Lack of procedures when materials arrive, maintenance schedules that are not updated, resulting in clogged hopper lines are one of the causes of product defects. In “improve” stage of DMAIC, regulations are evaluated to check raw materials before the production process starts and carry out regular maintenance activities.